A dual-band rectangular shape incorporated into circular patch antenna for 2.4/5 GHz wireless local area network applications - Suthasinee Lamultree; Nattakarn Somsanook; Wararak Narkkoht; Chuwong Phongcharoenpanich (Universitas Ahmad Dahlan, 2025)
This research exhibits a design of a dual-band patch antenna (DBPA) implemented by a rectangular shape incorporated into a circular patch together with a pair of half-wavelength inverted U-slots (HWIUSs) with the single feed for 2.4/5 GHz wireless local area network (WLAN) applications. For this work, the HWIUSs are key in designing a dual-band antenna. The DBPA is fed by a 50-Ohm microstrip line, printed on a copper layer overlaid on an FR4 substrate with a relative permittivity of 4.3 and height of 1.6 mm, while the bottom layer is backed by a partial ground plane. An antenna prototype with a dimension of 0.384λ_L×0.304λ_L×0.013λ_L was contrived and admeasured to verify the simulation. The measurement provides a nearly omnidirectional pattern with a 2.55 and 3.3 dBi peak gain covering a dual-band 10 dB return loss bandwidth of 15% (2.4–2.8 GHz) and 20% (4.96–5.86 GHz), respectively. Noticeably, simulated |S11| and radiation patterns are reasonable following experimental results showing its potential in 2.4/5 GHz WLAN services.